Fatigue Behavior of Weld Repaired AISI 4130 Aeronautic Steel Used in Critical Flight Safety Structures - Nascimento, Marcelino Pereira do [UNESP]; Batista, Carolina Cordeiro [UNESP]; Morais Pereira, Celso Pinto [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP]; Clark, G.; Wang, C. H. (Trans Tech Publications Ltd, 2014)
Since the 1950s, fatigue is the most important project and operational consideration for both civil and military aircrafts. For some aircraft models the most loaded component is one that supports the motor: the Motor Cradle. Because they are considered critical to the flight safety the aeronautic standards are extremely rigorous in manufacturing them by imposing a zero index of defects on the final weld quality (Safe Life), which is 100% inspected by Non-Destructive Testing/NDT. This study has as objective to evaluate the effects of up to four successive TIG welding repairs on the axial fatigue strength of an AISI 4130 steel. Tests were conducted on hot-rolled steel plate specimens, 0.89 mm thick, with load ratio R = 0.1, constant amplitude, at 20 Hz frequency and in room temperature, in accordance with ASTM E466 Standard. The results were related to microhardness and microstructural and geometric changes resulting from welding cycles.
Keywords: High strength steel; TIG Welding; HAZ; Airframe; Stress Concentration Factor